Phosphorus Starvation- and Zinc Excess-Induced Astragalus sinicus AsZIP2 Zinc Transporter Is Suppressed by Arbuscular Mycorrhizal Symbiosis - Xianan Xie (MDPI AG, 2021)
Zinc (Zn) is one of the most essential micronutrients for plant growth and metabolism, but Zn excess can impair many basic metabolic processes in plant cells. In agriculture, crops often experience low phosphate (Pi) and high Zn double nutrient stresses because of inordinate agro-industrial activities, while the dual benefit of arbuscular mycorrhizal (AM) fungi protects plants from experiencing both deficient and toxic nutrient stresses. Although crosstalk between Pi and Zn nutrients in plants have been extensively studied at the physiological level, the molecular basis of how Pi starvation triggers Zn over-accumulation in plants and how AM plants coordinately modulate the Pi and Zn nutrient homeostasis remains to be elucidated. Here, we report that a novel AsZIP2 gene, a Chinese milk vetch (Astragalus sinicus) member of the ZIP gene family, participates in the interaction between Pi and Zn nutrient homeostasis in plants. Phylogenetic analysis revealed that this AsZIP2 protein was closely related to the orthologous Medicago MtZIP2 and Arabidopsis AtZIP2 transporters. Gene expression analysis indicated that AsZIP2 was highly induced in roots by Pi starvation or Zn excess yet attenuated by arbuscular mycorrhization in a Pi-dependent manner. Subcellular localization and heterologous expression experiments further showed that AsZIP2 encoded a functional plasma membrane-localized transporter that mediated Zn uptake in yeast. Moreover, overexpression of AsZIP2 in A. sinicus resulted in the over-accumulation of Zn concentration in roots at low Pi or excessive Zn concentrations, whereas AsZIP2 silencing lines displayed an even more reduced Zn concentration than control lines under such conditions. Our results reveal that the AsZIP2 transporter functioned in Zn over-accumulation in roots during Pi starvation or high Zn supply but was repressed by AM symbiosis in a Pi-dependent manner. These findings also provide new insights into the AsZIP2 gene acting in the regulation of Zn homeostasis in mycorrhizal plants through Pi signal.